`A Special Zone for Confucianism'? Theses of the Academician Zhang Xianglong on Traditional Chinese Culture - Gänßbauer, Monika (Asian Studies, 2014)

Confucianism and Social Issues in China - the Academician Kang Xiaoguang. Investigations into NGOs in China, the Falun Gong, Chinese Reportage, and the Confucian Tradition. - Gänßbauer, Monika (Projekt Verlag, 2011)
Kang Xiaoguang, b. 1963, is a prominent academic and an independent thinker in mainland China. He once served as an advisor to Premier Zhu Rongji. Since the early 2000s Kang has been an ardent advocate of Confucianism and of the establishment of Confucianism as China's state religion. His books, however, cover a broad range of other topics, too. This publication offers the first book-length introduction into and discussion of topics and content of Kang's work. Kang Xiaoguang is a prolific scholar dealing with rural development in China and NGO project work and has also done extensive research on the religious movement Falun Gong, which he sees as an important agent for China's modernization. Another study he did is a piece of reportage literature. Here Kang looks into the case of Li Siyi, the death of a 3-year-old child and the failure of individuals and societal agents to prevent the tragedy. This study also collects together responses to Kang Xiaoguang's various theses from other authors belonging to the Chinese-speaking world.–Publisher's description.

Den Jadestein erlangen. Festschrift für Harro von Senger. - Gänßbauer, Monika (Otto Lembeck Verlag, 2009)

Die reisende Familie. Hongkonger Autorinnen erzählen. - Gänßbauer, Monika (Projektverlag, 2017)

Fate and Prognostication in the Chinese Literary Imagination - Lackner, Michael; Tam, Kwok-Kan; Gänßbauer, Monika; Siu Han Yip, Terry (Brill, 2020)
The essays collected in Fate and Prognostication in the Chinese Literary Imagination deal with the philosophical, psychological, gender and cultural issues in the Chinese conception of fate as represented in literary texts and films, with a focus placed on human efforts to solve the riddles of fate prediction. Viewed in this light, the collected essays unfold a meandering landscape of the popular imaginary in Chinese beliefs and customs. The chapters in this book represent concerted efforts in research originated from a project conducted at the International Consortium for Research in the Humanities at the Friedrich-Alexander-University Erlangen-Nuremberg, Germany. Contributors are Michael Lackner, Kwok-kan Tam, Monika Gaenssbauer, Terry Siu-han Yip, Xie Qun, Roland Altenburger, Jessica Tsui-yan Li, Kaby Wing-Sze Kung, Nicoletta Pesaro, Yan Xu-Lackner, and Anna Wing Bo Tso. <br

In China essen sie den Mond. Westliche Chinabilder vom 19. bis zum 21. Jahrhundert' - Gänßbauer, Monika (China heute : Informationen über Religion und Christentum im chinesischen Raum = Zhongguo-jiaoxun, 2010)

`In China They Eat the Moon': Western Images of China from the 19th through to the 21st Century - Gänßbauer, Monika (Asien : the German journal on contemporary Asia, 2011)

In Richtung Meer. Neue chinesische Essays. - Gänßbauer, Monika (Projekt Verlag, 2013)

Jahrbuch für Historische Kommunismusforschung (2009) - Gänßbauer, Monika (Bundesstiftung zur Aufarbeitung der SED-Diktatur, 2009)

Jia Pingwa: Drei Essays - Gänßbauer, Monika (Hefte für ostasiatische Literatur, 2010)

Kang Youwei und Kang Xiaoguang: Die Suche nach Zukunftsfähigkeit für China zwischen Zivilgesellschaft und Ziviltheologie - Gänßbauer, Monika (minima sinica, 2011)

Kinder der Bergschlucht. Chinesische Gegenwartessays. - Gänßbauer, Monika (Projekt Verlag, 2012)

Literatur- und Naturwissenschaft - Wissenskulturen in Wechselwirkung: Plädoyer für eine interaktionale Diskurszone zwischen den epistemischen Gemeinschaften - Gänßbauer, Monika (De Gruyter, 2015)

Monika Gaenssbauer on Contemporary Chinese Essayists - Gänßbauer, Monika (Asymptote Journal, 2013)

Popular Belief in Contemporary China - a Discourse Analysis. - Gänßbauer, Monika (Projekt Verlag, 2015)

Präsenz und implizites Wissen. Heilungsverfahren in christlichen Gruppierungen Chinas und deren Nähe zu volksreligiösen Praktiken - Gänßbauer, Monika (Präsenz und implizites Wissen. Zur Interdependenz zweier Schlüsselbegriffe der Kultur- und Sozialwissenschaften, 2013)

Präsenz und implizites Wissen: Zur Interdependenz zweier Schlüsselbegriffe der Kultur- und Sozialwissenschaften - Gänßbauer, Monika (transcript Verlag, 2013)
Präsenz - definiert als zeitliche und räumliche Gegenwart und Unmittelbarkeit - steht in einem Begründungszusammenhang mit implizitem Wissen. Innerhalb der Forschungsdiskussion um Präsenz etabliert der Band einen neuartigen Ansatz, indem er verschiedene Diskursivierungen von Präsenz in Religion, Kunst, Politik, Medien sowie Populärkultur aus dieser Interdependenz heraus zugänglich macht. Die Beiträge verfolgen dabei eine kulturvergleichende Perspektive, die speziell auf die Klärung der Kulturspezifik von Präsenzkonzepten abzielt und neue Möglichkeiten zur Analyse eines bisher wenig beachteten.

Theses of the Author Liu Zaifu in the Context of Exile Studies - Gänßbauer, Monika (Asien : the German journal on contemporary Asia, 2013)

Trägt chinesische Religions- und Christentumforschung zur Überwindung einer 'geistigen Krise' in der Reformära bei? - Gänßbauer, Monika (Den Jadestein erlangen. Festschrift für Harro von Senger., 2009)

Translation as a Creative and Performative Act - Some Deliberations - Gänßbauer, Monika (Translation Studies. Exploring Identities., 2015)

Translation Studies: Exploring Identities - Gänßbauer, Monika (writers.ink, 2015)

Von Goldlaufkäfern und Bilharziose: Ein Blick in das literarische Werk der chinesischen Autorin Can Xue - Gänßbauer, Monika (Literatur- und Naturwissenschaft - Wissenskulturen in Wechselwirkung: Plädoyer für eine interaktionale Diskurszone zwischen den epistemischen Gemeinschaften, 2015)

Welcoming the Exposure of the Counter Revolutionary..., A Chinese Theologian Coming to Terms with the Past - Gänßbauer, Monika (Jingfeng (Ching Feng), 2010)

Wilde Gedanken bei bewölktem Himmel: Notizen aus Hongkong: Aus dem Chinesischen und mit einer Einführung versehen von Monika Gänßbauer und Tang Wei - Gänßbauer, Monika; Leung, Ping-kwan (2016)

Wir begrüßen die Entlarvung der Konterrevolutionäre...' Vergangenheitsaufarbeitung eines chinesischen Theologen. - Gänßbauer, Monika (Jahrbuch für Historische Kommunismusforschung 2009, 2009)

Xin Qiji - Eine Einführung - Gänßbauer, Monika (Xin, Qiji: Kiefern im Schnee : Gedichte, 2011)

Xin Qiji: Kiefern im Schnee. Gedichte. - Gänßbauer, Monika (Projekt Verlag, 2011)

Zai Zhongguo renmen chi yueliang: 19 shiji dao 21 shiji Xifang de Zhongguo xingxiang ``在中国人们吃月亮''—— 19世纪到21世纪西方的中国形象 - Gänßbauer, Monika (世界汉学 = Shi jie Han xue = World Sinology, 2012)